Climate-smart agriculture practices based on precision agriculture: the case of maize in western Congo - Ulimwengu, John M.; Kibonge, Aziza (International Food Policy Research Institute, 2017)
Chapter 7 goes to the heart of the location specificity of CSA by investigating the potential benefits of using precision agriculture in the Democratic Republic of the Congo, finding that this approach can boost sustainable productivity through increased efficiencies in the use of inputs. Even though the use of precision agriculture may still be many years away, we can extrapolate an important lesson that applies to many other African countries: increased use of fertilizers, coupled with increased efficiency in their use, can lead to an optimal response to the effects of climate change.